527PA multicenter study of NRG1 fusions in Chinese non-small cell lung cancer patients and response to afatinib using next generation sequencing. (24th November 2019) - Li, X; Wang, W; Xu, C; Pu, X; Fang, S; Cai, X; Fang, Y; Zhu, Y; Wang, H; Liang, X; Zhuang, W; Zhang, Y; et al.
Abstract: Background: NRG1 fusions are potentially actionable genomic events seen in non-small cell lung cancers (NSCLC) and there are reports of therapeutic efficacy with agents that target Erb-B2/Erb-B3, while little is known about NRG1 fusions association with outcomes of afatinib. The aim of this study was to investigate the efficacy of afatinib in patients with advanced NRG1 fusion NSCLC. Methods: A multicenter study in China was initiated from February 2014, and NSCLC patients have been enrolled as of December 2018. To determine the frequency of the NRG1 fusions in NSCLC and other tumors, we analyzed data from 2743 clinical NSCLC cases, each of which had results from next-generation sequencing (NGS)-based 381 genes panel assay, analogous to the index patient. Results: Of this entire cohort, only one (0.04%) patient was identified with a CD74-NRG1 fusion. The patient was a 55-year-old never smoking male, who was diagnosed with lung adenocarcinoma from biopsies obtained, CD74-NRG1 fusion was found by NGS, the genes co-altered with NRG1 fusion was no concurrent with KRAS, EGFR, ALK, ROS1, RET, or other known drivers were identified in the study cohort cases, and NRG1 fusion driven NSCLC responding to afatinib will be presented. The patient was considered to have a partial response (PR) to afatinib, and he was alive up to now. Conclusions: NRG1 fusions were detected at a low incidence (0.04%) in Chinese patients. Patients with advanced NRG1 fusion NSCLC showed a good outcome of afatinib compared to those with ALK/ROS1 fusion which response to crizotinib, which will influence the development of strategies to detect these events on a large scale. Legal entity responsible for the study: Xingliang Li. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.